Make me dictator and I will save humankind. A rational approach to the emergency of the 21st century - Laurenc L. De Vita (The Central European Review of Economics and Management (CEREM), 2022)
Aim: Humankind finds itself in a dire situation. Solutions have been put forth, but none has made a significant impact on carbon release or resources depletion. I add my proposal, the literary device of the dictator, to those who feel there is some possible remedy for our predicament. Design / Research methods: This paper is part of a larger project which uses micro- and macro-sociology and cliodynamics, archaeology, evolutionary biology, and dissipative systems theory to describe both our global system, and its implications for our species. I briefly critique three other approaches regarding their likelihood of success. Conclusions / findings: The self-organized dissipative system drives population, population density, and the exploitation and depletion of natural resources. The system is the interface between humans and the environment. It is unlikely any approach which is not 1. dramatic, 2. inclusive, and 3. determinedly focused on disarming the global system will prevent the complete depletion of the natural world, and the continued mass extinction. Originality / value of the article: The paper challenges commonly held assumptions regarding the system and human participation in it. The paper should be of interest to anyone concerned about humankind. Implications of the research (if applicable): The paper has strong implications for policy. It describes how perpetuating ideas like "sustainable growth" can only ensure the collapse of the global system, and perhaps the collapse of the natural systems as well. The consequence of applying the research would be desperate, frighteningly objective, but will allow, perhaps, Homo to continue. Limitations of the research (if applicable): Future research could focus on re-interpreting data gathered by previous paradigms. Cliodynamics provides insight into the future by considering complex relationships. The limitations to the implications of the research lie in the fact that it is difficult for some to distinguish between "humankind" and the system.
Keywords: O13; P18; Q40; 330